The archaeological distribution (Scottish Historical and Archaeological Internet Reports, 2008)
This section considers the distribution of quartz across Shetland, the Western Isles, the Southern Hebrides, the western part of mainland Scotland and the Highlands. It appears that, in Scottish prehistory in general, quartz was mainly perceived as a utilitarian resource. The main trend in Scotland is that quartz dominates assemblages where other 'better' (more flakable) raw materials are absent or scarce, and the more abundant these other resources are, the more quartz is substituted by them, or even fully replaced (like on Islay where flint dominates completely.